Discriminación por causa de género en la ley 103 contra la violencia a la mujer y la familia. - Fierro Niza, Juan José (2014)
When requested by a male person, this is because society has estigmatized men as the only aggressor in the family, which has led to their rights being violated, the most important discussion focused on defining the scope Of existing regulations.